Treatment of Industrial Effluents in a Heavy Metal Sector Company: From Environmental Compliance to a Branding Strategy - Fontenelle, Anderson Rocha; Araujo, Gilberto Jorge da Cruz; Musci, Marcelo; Souza, Edmilson Monteiro de; Cardoso, Alexander Machado; Silva Neto, Dario Nepomuceno da (RGSA : Revista de Gestão Social e Ambiental, 2024)
Purpose: This work aims to conduct a review of the entire process of an effluent treatment plant installed in the manufacturing plant of a heavy metals sector company that treats the water used in the process of washing parts and equipment from customers sent for maintenance located in Rio de Janeiro city.